PUSAT HIBURAN, EDUKASI DAN TEATER SEBAGAI RUANG INTERAKSI SOSIAL DI KAWASAN MANGGA BESAR - Tuju, Gilbertus Davy Ryan; Mustaram, Agnatasya Listianti (Jurusan Arsitektur dan Perencanaan, 2025)
Since the Dutch era, Mangga Besar has been the center of entertainment destinations. There was once a park called Prinsen Park. This place became part of the history of theater and film, until it gave birth to the artist village